Comparative study of mifepristone followed by misoprostol with misoprostol alone for treatment of early pregnancy failure: an interventional randomised clinical study in a tertiary care hospital - Mirza, Robina; Sharma, Ankita; Sharma, Pooja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Early pregnancy failure (EPF) is a common experience for women. Medical management allows for expulsion of the nonviable pregnancy in a controlled manner without any surgical risk. The aim of this study was to compare efﬁcacy and safety of mifepristone followed by misoprostol with misoprostol alone in management of EPF. Methods: This was a prospective comparative interventional randomised clinical study conducted at Shri Maharaja Gulab Singh hospital, Jammu, Jammu and Kashmir India from November 2019 to October 2020. A total of 200 patients with gestational age less than 13 weeks and ultrasound diagnosis of EPF were included in the study and randomly divided into two groups, group A (100 patients) received tab. mifepristone 200 mg orally 24 hrs before the use of Tab misoprostol 800 ug per vaginally. If no expulsion occurs within 4 hours, repeat doses of 400 ug misoprostol were given per vaginally at 4-hourly interval to a maximum of 2 doses in women less than or equal to 9 weeks by ultrasound and 4 doses in women more than 9 weeks by ultrasound. Group B (100 patients) received only Tab misoprostol in similar doses without prior mifepristone. The study was performed after approval from the institutional ethical committee. The data was analysed using computer software Microsoft Excel, Statistical and IBM SPSS version 21.0. The statistical difference in mean value between two groups was tested using unpaired ‘t’ test. The qualitative data was compared using Fischer’s exact test. Results: The success rate was higher in group A 92% than group B where it was 76%. The mean induction-abortion interval and dose of misoprostol required for expulsion were 6.56±.66 hrs in group A and 10.40±4.33 hrs in group B and 1126.88±536.06 ug in group A and 1583.33±364.58 ug in group B. The patients in group A experienced significantly less side effects than those in group B, 19% versus 32% and also required fewer blood transfusions than group B, 2% versus 5%. Conclusions: In the present study we came to the conclusion that mifepristone followed by misoprostol is more effective, safe and acceptable than misoprostol alone.